2019
DOI: 10.1002/jcp.28222
|View full text |Cite
|
Sign up to set email alerts
|

miR‐545 promoted enterovirus 71 replication via directly targeting phosphatase and tensin homolog and tumor necrosis factor receptor‐associated factor 6

Abstract: Enterovirus 71 (EV71) is a small, nonenveloped icosahedral RNA virus and is the predominant causative pathogen of hand‐foot‐and‐mouth disease. Recently, microRNAs (miRNAs) are reported to play important roles in the pathogenesis of EV71 replication. This study investigated the role of miR‐545 in the EV71 replication and explored the underlying molecular mechanisms. We showed that miR‐545 was upregulated in the EV71‐infected human embryonic kidney (HEK) 293 cells and rhabdomyosarcoma (RD) cells. Overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Emerging evidences indicate that the host microRNAs (miRNAs) have a significant effect on the comprehensive host-pathogen interaction [ 7 ], even participating in the viral life cycle. For instance, miR-101 represses feline herpesvirus 1 reproduction by targeting cellular suppressor of cytokine signaling 5 to promote IFN-I signaling [ 20 ]; miR-7 suppresses rotavirus replication via targeting viral NSP5 directly [ 21 ]; miR-122 reduces HBV gene expression and replication via binding with hepatitis B virus pre-genomic RNA sequence [ 22 ]; miR-21-3p promotes influenza A virus H5N1 replication by regulating FGF2 to repress IFN-I signaling [ 23 ]; miR-545 promotes enterovirus 71 propagation through directly targeting phosphatase and tensin homolog and tumor necrosis factor receptor-associated factor 6 [ 24 ]. In the case of FMDV, there are only a few studies, artificial miRNA targeting 3D polymerase is efficient to inhibit FMDV replication [ 25 ], miR-1307 and miR-203a repress FMDV infection [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences indicate that the host microRNAs (miRNAs) have a significant effect on the comprehensive host-pathogen interaction [ 7 ], even participating in the viral life cycle. For instance, miR-101 represses feline herpesvirus 1 reproduction by targeting cellular suppressor of cytokine signaling 5 to promote IFN-I signaling [ 20 ]; miR-7 suppresses rotavirus replication via targeting viral NSP5 directly [ 21 ]; miR-122 reduces HBV gene expression and replication via binding with hepatitis B virus pre-genomic RNA sequence [ 22 ]; miR-21-3p promotes influenza A virus H5N1 replication by regulating FGF2 to repress IFN-I signaling [ 23 ]; miR-545 promotes enterovirus 71 propagation through directly targeting phosphatase and tensin homolog and tumor necrosis factor receptor-associated factor 6 [ 24 ]. In the case of FMDV, there are only a few studies, artificial miRNA targeting 3D polymerase is efficient to inhibit FMDV replication [ 25 ], miR-1307 and miR-203a repress FMDV infection [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In EV71 infection, miRNAs may be a double-edged sword. For example, Sun et al found that EV71 infection increased the level of miR-545 in HEK 293 cells, and EV71 replication was promoted by overexpression of miR-545 [43]. Another study performed by Zhao et al reported that miR-494-3p promoted EV71 replication by directly targeting PTEN [2].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the protein-coding gene of eukaryotic translation initiation factor 4E (eIF4E) could be repressed by EVA71-induced miR-141, leading to continuous virus replication [54]. Upregulated miR-545 promoted EVA71 replication at least partly via targeting phosphatase and tensin homolog (PTEN) and tumor necrosis factor receptor-associated factor (TRAF)6 [55]. Several miRNAs such as miR-526a [56], miRNA-548 [57], miR-146a [58], and miR-21 [59] indirectly affected EV replication by influencing host innate immunity through various independent mechanisms.…”
Section: Known Impacts Of Ncrnas On Ev Replicationmentioning
confidence: 99%
“…Upregulated miR-628-5p upon EVA71 infection could target the 3'UTR of TRAF3, which further suppressed TRAF3-mediated IFN-β transcription in rhabdomyosarcoma cells(RD) [99]. EVA71 induced miR-545 in 293T cells and RD cells, which directly targeted the 3'UTR of TRAF6, leading to persistent viral replication [55]. It has also been reported that the expression of miR-146a, which targets interleukin-1 receptor-associated kinase 1 (IRAK 1) and TRAF6 involved in TLR signaling and type I IFN production, was significantly upregulated in EVA71-infected cells [58].…”
Section: The Impact Of Ncrnas On Host Innate Immune Responses Inducedmentioning
confidence: 99%